Pork as a source of nutrients in a human diet - comparison of meat obtained from conventional and organic systems offered in the Polish market - Weronika Zduńczyk; Katarzyna Tkacz; Renata Pietrzak-Fiećko; Benedetta Bottari; Monika Modzelewska-Kapituła (NFS Journal)
Pork plays a key role as an important protein source of high biological value, essential fatty acids, vitamins (B group) and microelements such as zinc, selenium and iron in the human diet. Therefore, this study aimed to investigate and compare the chemical composition, fatty acid profile, mineral content and technological properties of organic and conventional pork loin, with particular emphasis on their availability in the Polish market. In the study, a hypothesis that organic meat has a more beneficial composition from a nutritional perspective and better technological properties was tested. The research material consisted of pork loin (musculus longissimus dorsi et lumborum) available on the Polish market. The technological properties (pH, colour, free water, shear force) and nutritional value (proximate composition, the fatty acid profile and mineral compounds) were assessed. Organic pork was darker and leaner, and had lower pH and water-holding capacity. It contained higher Cu, which resulted in a higher coverage of requirements for Cu. It was characterized by a more favourable fatty acid composition, including a higher concentration of monounsaturated fatty acids and a lower level of saturated fatty acids and better atherogenic and thrombogenic indexes, which indicates its better nutritional value than conventional pork.